HUBUNGAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG GIZI DENGAN KEJADIAN KEKURANGAN ENERGI KRONIK (KEK) PADA USIA REMAJA - Dewi, Rosmala Kurnia; Martini, Sri (Coping: Community of Publishing in Nursing, 2021)
Adolescents who have poor nutritional status or malnutrition has been too long will be a Chronic Energy Deficiency (CED). Chronic Energy Deficiency is a condition in which a person suffers from a chronic lack of energy and protein nutrition. The purpose of this study was to determine the relationship between of knowledge of adolescents about CED with the incidence of CED. This research uses analytical research methods with a retrospective approach. Bivariate analysis is used to determine the relationship to the object by using the chi-square test. This research was held in the youth organization of Nganggil Hamlet, Karanganyar Village, Purwodadi District, Grobogan Regency using secondary and primary data with questionnaire sheets as research data. The research subjects were adolescent girls with a sample of 43 respondents using a total sampling system. The results of the study, it was found that nutritional knowledge with the incidence of CED was obtained as many as 4 people (13.3%) with a good level of nutritional knowledge in adolescent girls with CED, while the level of knowledge on nutrition was sufficient and there was no evidence of CED. The results of statistical tests p-value > 0.297. It means that there is no relationship between nutritional knowledge and CED. Keywords: Adolescent, CED, Knowledge Level, Nutrition